OGPADSM2: oriented-group public auditing for data sharing with multi-user modification. (2017) - Zhang, Jianhong; Zhao, Xubing; Zhen, Weina
In most data sharing protocols for cloud storage, to update the outsourced data, the data updating operation is only executed by data owner. Obviously, it is far from practical owing to the tremendous computational cost on data owner. Until now, there are a few protocols in which multiple cloud users are allowed to update the outsourced data with integrity assurance. And these protocols do not consider collusion attack between misbehaving cloud servers and the revoked users, which is an important challenge in data sharing protocol. To support multi-user modification and resist collusion attack, we propose a novel public auditing for data sharing with multi-user modification in this paper. Our scheme does not support public checking and efficient user revocation, but provides backward security. At the same time, our scheme is provably secure under the bilinear Diffie-Hellman problem. To increase efficiency of the auditor's verification, an improved protocol is given. In the improved protocol, only one pairing operation is required in the auditor's verification phase. By comparison with the other protocols, our scheme has lower computation cost on the auditor and stronger security.